2005
DOI: 10.1051/0004-6361:20041639
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Keplerian accretion disk and precessing outflow in the massive protostar IRAS 20126+4104

Abstract: Abstract. We report on interferometric observations at 3.2 and 1.3 mm of the massive young stellar object IRAS 20126+4104 obtained in the C 34 S and CH 3 OH lines and in the continuum emission. The C 34 S data confirm the existence of a Keplerian disk, as already suggested by various authors. However, the mass of the central object is ∼7 M , significantly less than previous estimates. We believe that such a discrepancy is due to the fact that the rotation curve is affected not only by the star but also by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
264
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 197 publications
(294 citation statements)
references
References 22 publications
27
264
3
Order By: Relevance
“…In conclusion, despite some differences between the old and new best-fit parameters, the corrected data confirm that the jet is very beamed, lies close to the plane of the sky, and is approximately perpendicular to the disk (whose PA is ∼53 ± 7 • , see Cesaroni et al 2005).…”
Section: Disk and Jet Structure In Iras 20126+4104mentioning
confidence: 66%
See 1 more Smart Citation
“…In conclusion, despite some differences between the old and new best-fit parameters, the corrected data confirm that the jet is very beamed, lies close to the plane of the sky, and is approximately perpendicular to the disk (whose PA is ∼53 ± 7 • , see Cesaroni et al 2005).…”
Section: Disk and Jet Structure In Iras 20126+4104mentioning
confidence: 66%
“…-IRAS 20126+4104 is associated with a Keplerian disk rotating about a ∼7 M protostar (Cesaroni et al 1997Zhang et al 1998); -the disk is also seen in silhouette as a dark lane at nearand mid-IR wavelengths (Sridharan et al 2005;De Buizer et al 2007); -the YSO is powering a bipolar jet/outflow, imaged in a variety of tracers from ∼1 down to ∼100 mas from the star (Wilking et al 1990;Cesaroni et al 1997Cesaroni et al , 1999Cesaroni et al , 2005Shepherd et al 2000;Su et al 2007;Shinnaga et al 2008;Hofner et al 1999Hofner et al , 2007Moscadelli et al 2000Moscadelli et al , 2005Trinidad et al 2005); -the jet/outflow appears to be undergoing precession (Shepherd et al 2000;Cesaroni et al 2005;Lebrón et al 2006), perhaps caused by the presence of another YSO A&A 526, A66 (2011) detected at radio and IR wavelengths (Hofner et al 1999;Sridharan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…High-mass stars (O-and B-type stars with masses > ∼ 8 M ) are crucial for the understanding of many physical phenomena in the Galaxy; however, their first stages of formation are still poorly A&A 569, A11 (2014) identified and studied (e.g., Simon et al 2000), there are only a few convincing disks (with sizes ≤1000 AU) found around B-type protostars (e.g., Schreyer et al 2002;Cesaroni et al 2005Cesaroni et al , 2007Carrasco-González et al 2012;Wang et al 2012). Moreover, convincing evidence of centrifugally supported disks around O-type protostars still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…They should have low optical depths, and trace only the hot gas around the central protostar, and not its envelope. In the past, molecules such as NH 3 , CH 3 CN, HCOOCH 3 , and C 34 S have been proposed for this purpose (i.e., Zhang et al 1998;Cesaroni et al 1997Cesaroni et al , 1999Beuther et al 2004Beuther et al , 2009). …”
Section: Introductionmentioning
confidence: 99%